Vacuum-assisted sulfur crystallization process to improve the electrochemical performance of S@PC composite cathode materials for Li–S batteries. (April 2022) - Zhang, Hui; Gao, Geng; Song, Tingyu; Zhang, Keyu; Li, Yin; Yao, Yaochun
Abstract: The melt-diffusion method and vapor-phase infusion method are high-frequency approach to composite sulfur to porous materials, but in these methods the crystallization process of sulfur occurs naturally and cannot be controlled. In this work, we prepared the S@PC composites via a facile dissolution-crystallization method and vacuum was used to assist the sulfur crystallization process. Comparing the composites prepared under vacuum and atmosphere, the results show that crystallized sulfur obtains a finer particle size under vacuum condition, which leads to an obviously increase in the initial discharge capacity, rate performance and cycle stability of the battery. The improvement of electrochemical performance is attributed to the fact that the finer sulfur provides quantities interface contact with conductor matrix and sufficient reaction sites between the electrode and electrolyte, accelerating charge transfer and the electrolyte diffusion. This research provides a technical support for the simplified and controllable preparation of cathode materials for lithium-sulfur batteries. Highlights: The S@ PC was prepared via dissolution-crystallization method and vacuum was used to assist the crystallization process. The crystallized sulfur obtains a finer particle size under vacuum condition. The batteries with composites cathod made in vacuum have an obviously increase of the electrochemical performance.